Mitigation of Halal Risk in the Production Process of Processing Beef Using the FMEA Method in UMKM Dendeng Sapi Asri - Hafidh Munawir; Fatimah Tri Astuti; Eko Setiawan; Mila Faila Sufa (WARTA LPM, 2021)
Purpose : This research was conducted to identify the risk of being halal that occurs in the production process, calculate the level of halal risk, and provide suggestions for improvements to reduce the risk of the halalness of a production process.Methodology : This study uses the FMEA method which aims to analyze the risk of events that may occur in the production process and the AHP method is used to determine mitigation priorities that can be applied as a proposed improvement in UMKM Dendeng Sapi Asri.Results : The results of risk identification found that there were 19 halal risk and five priority risks, namely raw materials that are not registered with LPPOM MUI, mismatches of raw materials received, because animal dung falls from above during drying of meat, the production process has not used work SOPs for each stage of the process. halal, and the shipping process that is potentially contaminated with unclean.Applications/Originality/Value : At the end of the study, suggestions for improvement were given to reduce the risk of halalness, namely overseeing the implementation of work SOP for employees, and followed by routine cleaning, implementing work SOP, establishing cooperation, checking products before sending, establishing communication, providing training to workers, and positioning drying tools in an appropriate place.